Clinical outcomes from the texting for relapse prevention (T4RP) in schizophrenia and schizoaffective disorder study. (October 2020) - Cullen, Bernadette A.; Rodriguez, Katrina; Eaton, William W.; Mojtabai, Ramin; Von Mach, Tara; Ybarra, Michele L.
Highlights: The program decreased the experience of positive symptoms of schizophrenia. Medication adherence, especially injectable medication adherence improved. There was no significant difference in hospitalization rates between the 2 groups. Abstract: This 6 month randomized control trial investigated whether a novel text-messaging program impacted targeted clinical outcomes in patients with schizophrenia and schizoaffective disorder (SAD). Forty patients were enrolled and completed baseline, 3-month and 6-month assessments. The intervention group received daily symptom check-in text messages, plus, a medication reminder or, inspirational quote text. The control group had treatment as usual. At 6 months the Positive and Negative Syndrome Scale mean positive score was significantly lower and injectable medication compliance was significantly higher in the intervention group. Recovery scores were significantly higher at 3 months. Results suggest that this program may benefit individuals with schizophrenia/SAD who use text messaging. Further investigation in a larger sample appears warranted.